Pemanfaatan Minyak Kayu Putih (Melaleuca leucadendra Linn) sebagai Alternatif Pencegahan ISPA: Sebuah Studi Etnografi di Pulau Buru, Provinsi Maluku - Agustina, Zulfa Auliyati; Suharmiati, Suharmiati (Jurnal Kefarmasian Indonesia, 2017)
The Acute Respiratory Infections (ARIs) is a disease which commonly infects children. Based on Indonesian basic health research 2013, the national and Buru Island's period prevalence of ARIs were 25% and 24,8%. The other side, cajuput oil has been traditionally used to reduce respiratory tract disorders and infections. This research used the ethnographic approach with observation participation and direct communication to collected the data. The results showed a high number in ARIs cases in Buru Island area were affected by many factors, some of them are the lack of Clean and Healthy Behaviour (PHBS) and had a little faith in health services, especially for people who live in the mountain area. It was because of minimum intervention from public health services. This research showed the Cajuput oil was potentially used as an alternative prevention of ARIs in Buru Island by inhalation method. The main content of Melaleuca leucadendra Linn had a benefit to be the mucolytics, bronchodilator, anti-inflammation and antitussive.